(untitled) (Global Journal of Medical Research, 2018)
Invasive cervical cancer is the second-most common cancer in women world-wide, 80% of these cases were discovered through records to be from developing countries although it can be readily detected in the premalignant phase, cervical cancer remains the second most common cancer in Nigeria and fifth in the United Kingdom. The objective of this study is to determine awareness and perception affecting utilization of cervical cancer screening services awareness, perception and factors affecting utilization of cervical cancer screening services among nurses in Adobo Maternity Teaching Hospital, Ibadan, Oyo State, Nigeria. The research was a descriptive and cross-sectional studyconducted in Adobo Maternity Teaching Hospital Ibadan, Nigeria. The study showed a high level of perception 106 (59.9%) among the nurses within this study and the nurses that had positive perception only 8 (19.0%) had undergone cervical cancer screening in the past.